Analisis Penjaminan Penanaman Modal menurut UU No 25 Tahun 2007 - Syamsul Azhari Damanik; Emiel Salim Siregar; Firhan Azwa Samosir; Wahyu Wahyu; Alya Amanda (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Investment activities play an important role in supporting national economic development and increasing economic growth in Indonesia. However, investors often face various legal risks, including policy inconsistency, complicated licensing procedures, and uncertainty in investment protection. This study aims to analyze the forms of investment guarantees regulated under Law Number 25 of 2007 concerning Investment and to examine their implementation in providing legal protection for investors. The research employed a normative legal method using statutory and conceptual approaches. Data were collected through library research based on primary, secondary, and tertiary legal materials related to investment law. The findings indicate that the government provides several forms of protection to investors, including guarantees of legal certainty, protection against nationalization, freedom of asset transfer and repatriation, and dispute settlement mechanisms through arbitration or other agreed procedures. These guarantees are intended to create a secure and conducive investment climate. Nevertheless, the implementation of investment guarantees still encounters several obstacles, such as bureaucratic inefficiency, inconsistent regional policies, and weak supervision of investment activities. Therefore, strengthening legal certainty and improving investment governance are necessary to enhance investor confidence in Indonesia.